English local government funding: Trends and challenges in 2019 and beyond - Tom Harris; Louis Hodge; David Phillips (Institute for Fiscal Studies (IFS), 2019)
The 2010s have been a decade of major financial change for English local government. Not only have funding levels - and hence what councils can spend on local services - fallen significantly; major reforms to the funding system have seen an increasing emphasis on using funding to provide financial incentives for development via initiatives such as the Business Rates Retention Scheme (BRRS) and the New Homes Bonus (NHB). Looking ahead, increases in council tax and additional grant funding from central government mean a boost to funding next year - but what about the longer term, especially given plans for further changes to the funding system, including an expansion of the BRRS in 2021-22? This report, the first of what we hope will be an annual series of reports providing an up-to-date analysis of local government, does three things in this context. First, it looks in detail at councils' revenues and spending, focusing on the trends and choices taken over the last decade. Second, it looks at the outlook for local government funding both in the short and longer term. And third, it looks at the impact of the BRRS and NHB on different councils' funding so far, to see whether there are lessons to guide reforms to these policies. The report focuses on those revenue sources and spending areas over which county, district and single-tier councils exercise real control. We therefore exclude spending on police, fire and rescue, national park and education services and the revenues specifically for these services. When looking at trends over time, we also exclude spending on and revenues specifically for public health, and make some adjustments to social care spending to make figures more comparable across years. Public health was only devolved to councils in 2013-14, and the way social care spending is organised has also changed, with councils receiving a growing pot of money from the NHS to help fund services.
Keywords: 330